Response of Wheat Genotypes to Different Levels of Nitrogen - Shrestha, Shukra Raj; Manandhar, Sarita; Chaudhary, Bedanand; Sapkota, Bibek; Bhattarai, Rudra; Adhikari, Suraya Prasad (Journal of Nepal Agricultural Research Council, 2016)
A field experiment was conducted using six genotypes of wheat (Triticum aestivum L.) for response to different levels of nitrogen (N) use. The experiment was laid out in split plot design with four levels (0, 50, 100 and 150 kg N ha-1) as main plots and six wheat genotypes (BL 3623, BL 3629, BL 3872, NL 1008, NL 1055 and Vijay, a check variety) as sub-plots. Grain yield and other yield components increased linearly in response to N concentrations in both seasons. Only two parameters: days to heading (DOH) and days to maturity (DTM) varied significantly (p ≤ 0.05) among wheat genotypes in both the years. None of the parameters showed interaction effects in both seasons. Vijay showed highest grain yield of 3.12 t ha-1 in 2013 with the application of 100 kg N ha-1, and 3.23 t ha-1 in 2014 with 150 kg N ha-1. Spike length, productive tillers m-2, number of spikes m-2 and test weight were greater with higher N rates. The straw yield of wheat fertilized with 150 kg N ha-1 was the highest in Vijay (4.35 t ha-1) and BL 3872 (4.33 t ha-1), respectively. Vijay with 100 kg N ha-1 produced the highest number of productive tillers m-2 (276.33) in 2013 and 296.00 with the application of 150 kg N ha-1 in 2014.